Tandem Nucleophilic Addition/Fragmentation of Vinylogous Acyl Nonaflates for the Synthesis of Functionalized Alkynes, with New Mechanistic Insight - Batsomboon, Paratchata; Gold, Brian A.; Alabugin, Igor V.; Dudley, Gregory B. (Synthesis, 2012)
Vinylogous acyl nonaflates, like the corresponding triflates, are subject to nucleophile-triggered fragmentation as part of a tandem process for generating functionalized alkynes. Advantages to the use of nonaflates in lieu of triflates include cost and stability. Computational analysis supports a postulated fragmentation mechanism involving a closed (cyclic) transition state with concerted extrusion of lithium sulfonate.
Keywords: alkynes; fragmentation; nucleophilic addition; solvent effects; tandem reaction